Foreign Banks in the CESE Countries : In for a Penny, in for a Pound? - Ong, Li.; Maechler, Andrea (Washington, D.C. : International Monetary Fund, 2009)
The aim of this paper is to construct a comprehensive and consistent dataset to analyze the potential risks from foreign bank lending, for both the creditor and borrower countries of Central, Eastern and South-Eastern Europe (CESE). We develop a picture of bank claims on 13 CESE countries by combining credit statistics from several sources. Our constructed data suggest that some of these host countries have become more at risk from a sudden withdrawal of short-term external funding, while home countries have significant aggregate exposures to the region. Overall, we find that data on banking activity remain largely inadequate for surveillance and policymaking purposes, and that a concerted effort to improve data collection is needed at the international level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet